The Effect of Current Ratio, Working Capital Turnover and Debt to Equity Ratio on Profitability in Manufacturing Companies - Ricky Jeremy Panogari Sinambela; Erniati; Ike Rukmana Sari (Journal of Research in Business, Economics, and Education, 2021)
This study aims to determine whether there is an effect of Current Ratio, Working Capital Turnover and DER on profitability using ROA proxy in manufacturing companies in the various industrial and chemical sectors with a period of 5 years, namely 2015-2019. The method used is descriptive quantitative and the nature of causal relationship research. This sector on the IDX has a population of 71 companies and only 30 companies can be sampled based on purposive sampling technique. For data processing using the SPSS version 21 application with multiple linear regression analysis techniques. The results of data processing partially show that only DER has an influence on profitability in a negative and significant direction, while the Current Ratio and working capital turnover have no implications at all on profitability. Simultaneously the three variables affect the profitability with the magnitude of the influence seen from the value of the coefficient of determination is 10%.